Social innovation and sustainability with women in areas of social vulnerability: the Thousand Women Program in São João dos Patos - MA (Revista de Ensino em Artes, Moda e Design, 2024)
The article addresses how social innovations are changing the lives of people and communities, with a focus on sustainability, requiring changes in ways of life to preserve the environment and society. The objective is to present social innovation and sustainability initiatives in fashion, promoted by the Mulheres Mil Program in partnership with the Fashion Revolution movement, through a photo contest. The research reflects on the autonomy and quality of life of socially vulnerable women. analysis of the captured images, organized into categories such as affection, identity and trust. The results show that these images provided interpretations about the social and questioned who can speak for “others”. female empowerment, in addition to encouraging entrepreneurship and conscious consumption."
Keywords: social innovation; sustainability; fashion; Thousand Women Program